Corrosion behavior of alloy AA6063-T4 in HCl and NaOH solutions - Kisasoz, Alptekin (WALTER DE GRUYTER GMBH, 2018)
AA6XXX aluminum alloys are widely used in the automotive and aeronautic industries and for food packaging thanks to their lightness, specific strength, and corrosion resistance. The mechanical properties of AA6XXX alloy increase through an age hardening process thanks to the formation of Mg2Si particulates. These particulates enhance mechanical strength and likewise change corrosion resistance. In this study, the corrosion behavior of AA6063-T4 alloy in acidic and alkaline media was investigated and the results were compared with AA6063-T651 alloy. Acidic media was prepared in a 0.1M HCl solution; alkaline media was prepared in a 0.1M NaOH solution. Corrosion tests were performed for 360 hours in both solutions. Corrosion properties were determined by measuring weight loss and surface roughness values of the samples and pH values of the solutions. In both environments, artificially aged samples were found to have higher corrosion rates. There was a direct relationship between corrosion loss and surface roughness values.
Keywords: Aluminum; AA6063; corrosion; surface roughness; natural aging; MECHANICAL-PROPERTIES; HEAT-TREATMENT; INTERGRANULAR CORROSION; AL-ALLOY; MG; Materials Science